Study on current geostress characteristics and fracturing countermeasures in low-permeability reservoirs - Xiangwu Bai; Zhiping Li; Fengpeng Lai (Journal of Petroleum Exploration and Production Technology)
Abstract The study investigates the geostress characteristics and fracturing countermeasures in a low-permeability sandstone reservoir within the YP1 well area of the Songliao Basin. The reservoir exhibits multiple layers, thin individual layer thicknesses, and a concentrated oil-bearing section, posing challenges for development. To address these complexities, the research utilizes seismic, well logging, and hydraulic fracturing data to calculate key parameters for ground stress field simulation. The study proceeds in three stages: simulation of the present-day tectonic stress field and classification of deformation medium types; depth-slice-based simulation of the present-day tectonic stress field for each layer; and establishment of a 3D stress model using Petrel software. This model allows for the analysis of the spatial distribution of the tectonic stress field and the identification of spatial variation rules within the YP1 well area’s present-day tectonic stress differential stress values. These findings provide a foundation for optimizing layer selection in vertical well fracturing projects within low-permeability reservoirs. Furthermore, the study examines the stress state of the straight wellbore in the YP1 well zone, proposes corresponding fracturing methods based on distinct stress states, and evaluates the fracturing effects observed in the YP1-4 and YP1-5 wells. These insights offer valuable support for the large-scale development of the YP1 well zone and the strategic deployment of horizontal wells.